How People Use Web-Based Parenting Information to Support Others in Their Social Circle: Qualitative Descriptive Study - Reem El Sherif; Pierre Pluye; Virginie Paquet; Fidelia Ibekwe; Roland Grad (JMIR Publications, 2023)
BackgroundAlmost two-thirds of the North American population have searched for health information on the web, and the majority report searching on behalf of someone else in their social circle, a phenomenon referred to as proxy seeking. Little is known about how proxy seekers use web-based health information and the outcomes they experience. ObjectiveThe main aim of this study was to explore why proxy seekers used a parenting website on behalf of parents in their social circle and the outcomes they reported. MethodsA qualitative descriptive study was conducted in the context of a partnership with a web-based parenting resource to explore the contexts and motivations for proxy web-based health information seeking, use of information, and subsequent outcomes. A total of 14 participants who self-identified as family members, friends of parents of young children, or professionals who worked with young children were interviewed, and a thematic analysis was conducted. ResultsThe following 4 reasons for proxy seeking were uncovered: for reassurance, out of personal curiosity, as part of a professional role, or following an explicit request from the parents. Information was used to provide informational support for parents or material support for a child. Positive outcomes of using the information and some of the resulting interpersonal tensions were described. ConclusionsThis study provides an in-depth look at proxy seeking behavior and outcomes among users of a web-based parenting resource.